Analisis Peranan Sektor Pertanian Terhadap Pertumbuhan Ekonomi Di Kabupaten Aceh Barat - Mauliya, Mara; Agustina, Irma; Sandy, Dea Maulina; Mahrizal, Mahrizal (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
The agricultural sector plays a crucial role in the regional development of Aceh Province. Its contribution to the Gross Regional Domestic Product (GDRP) of Aceh continues to exceed that of the commercial sector. Economic growth, reflected in changes in GDRP from one period to the next, serves as a true indicator of the development of a region. The aim of this study is to assess the extent to which the agricultural sector influences economic growth in West Aceh district, based on partial hypothesis testing (t-test).The research method employed in this study is a quantitative descriptive approach. The results of the hypothesis test (t-test) demonstrate that the independent variable, the Agricultural Sector (X), significantly impacts the dependent variable, Economic Growth (Y). Therefore, it is essential for local government support to foster the development of the agricultural sector in the western region of Aceh.